Innovating problem solving for sustainable green roofs: potential usage of TRIZ – Theory of inventive problem solving - Mansoor, Muhammad; Mariun, Norman; AbdulWahab, Noor Izzri (Elsevier, 2017)
Green roofs are recognized as worthy strategy for making buildings more environmental friendly and sustainable, but there remain a lot of key concerns and limitations in usage of green roofs. Following different driving initiatives for green roofs, researchers are passionately exploring ways to cater deficiencies in existing technologies. The research offered using ‘Theory of Inventive Problems Solving (TRIZ)’ for seeking further developmental directions and potential future dimensions for green roofs technologies. It presented possible ways to model green roofs related problems with different TRIZ tools, demonstrating ways to seek guidance from TRIZ database of inventive principles and breakthrough solution directions. The research adds value to researchers’ working for green roofs in further developments. It provides a way to reach breakthrough solutions beyond one’s personal limited knowledge and expertise by broadening the horizon of solution search through TRIZ.